Lost in the dark: Antipatharia-Symbiodiniaceae association in the deep waters of the Red Sea - Vicario, Silvia; Terraneo, Tullia I.; Bocanegra Castano, Carolina; Chimienti, Giovanni; Oury, Nicolas; Vimercati, Silvia; Hume, Benjamin C. C.; Marchese, Fabio; Nolan, Megan K. B.; Eweida, Ameer A.; Purkis, Sam J.; Rodrigue, Mattie; et al. (Frontiers in Marine Science, 2024)
Black corals (Hexacorallia: Antipatharia) are a major component of mesophotic and deep marine ecosystems. Due to their preference for light deprived environments, black corals have historically been considered azooxanthellate, yet recent works have found them associated with dinoflagellates of the family Symbiodiniaceae down to 396m depth. While corals and Symbiodiniaceae generally establish a symbiotic relationship in shallow water environments, the implications of this association is less well understood at deeper depths, where low light penetration cannot sustain efficient photosynthetic activity for the algae. However, Symbiodinaceae are not obligate autotrophs, and their capacity for heterotrophic feeding categorizes them as mixotrophs. In this study, we investigated the presence and diversity of Symbiodiniaceae associated with the deep-sea black coral Bathypathes thermophila, collected from 204 to 655m depth in the Saudi Arabian Red Sea. Using high-throughput sequencing of the ITS2 region, we report (1) the deepest record to date of Symbiodiniaceae associated with an anthozoan from 655m, comprising and (2) the first Red Sea record of Antipatharia in association with Symbiodiniaceae. Our analyses revealed that 14 out of 27 colonies of B. thermophila were associated with Symbiodiniaceae of the genera Cladocopium and Durusdinium. We unveiled 16 novel ITS2 type profiles, possibly unique to black corals and/or to these depths, along with seven profiles that were already known from shallow-water Scleractinias. Our study supports the existence of black corals-Symbiodiniaceae association and warrants further research to better understand the evolutionary processes and physiological mechanisms driving this association, specifically in light deprived environments.